Rheological and electrical percolation of reinforced soft polyvinyl chloride composites with different morphological carbon fillers - Yu Wang; Xue-Fei Ping; Lu liu; Hai-Long Ping; Fu-Yong Liu; Hong-Wei He; Pi Wang; Wen-Wen Yu (Journal of Materials Research and Technology, 2024)
The study analyzed the electrical properties, mechanical performance, and rheological behavior of three kinds of high plasticizer-content polyvinyl chloride (PVC) composites, herein referred as SCBC, EGC and MCNTC, respectively filled with porous superconductive carbon black (SCB), flake-like expanded graphite (EG), and tubular multi-walled carbon nanotubes (MCNT). The impact of the conductive fillers' morphology on the electrical percolation and viscoelastic percolation performance of the composites were investigated to understand the conductive mechanisms. It revealed that the incorporation of SCB and MCNT can induce both viscoelastic and electrical percolation in the composites. The thresholds for viscoelastic percolation for SCBC and MCNTC are between 2.35-3.11 vol% and 2.72–3.59 vol%, respectively, which are lower than their electrical percolation thresholds of 3.85 vol% for SCBC and 3.65 vol% for MCNTC. The nature of PVC chains, which can transmit force but not electrons, results in a higher electrical percolation threshold than the rheological percolation threshold. Despite MCNT's poorer dispersion, its high aspect ratio and one-dimensional tubular shape enabled it to achieve electrical percolation at a lower loading level. Due to the poor dispersion, EG did not cause either viscoelastic or electrical percolation in the composites within the 0–9 vol% range.